Teachers’ Perceptions of The Implementation of Character Education in Islamic Religious Learning at SMP Muhammadiyah 1 Denpasar Bali - Safitri, Novianty; Alam, Naufal Ahmad Rijalul (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2024)
This study examines on Strengthening Character Education (PPK) in Islamic education. Strengthening Character Education (PPK) is a systematic approach to shaping and developing positive character in individuals, particularly in the setting of education. This qualitative research used a qualitative descriptive approach to investigate the subject of one of the SMP Muhammadiyah 1 Denpasar, Bali. Data was gathered through interviews, observations, and documentation. The findings demonstrate that SMP Muhammadiyah 1 Denpasar, Bali has adopted Strengthening Character Education (PPK) in its Islamic curriculum. Implementing PPK improves learning outcomes and student behaviour by enhancing learning motivation, moral strength, social skills, and self-confidence. The curriculum that includes character education and supports extracurricular activities is the key to success in shaping student’s character.